Teacher Motivation and Burnout of English-as-a-Foreign-Language Teachers: Do Demotivators Really Demotivate Them? - Sato, Masatoshi; Fernández Castillo, Francisca; Oyanedel, Juan Carlos (Frontiers in Psychology, 2022)
This study examined the relationships between teacher motivation (TM) and perceived burnout of English-as-a-foreign-language (EFL) teachers in Chile. A particular focus was given to demotivators and their impact on TM and burnout. The impact of COVID-19 was considered. Given that EFL teachers tend to be second language (L2) learners of English themselves, the study also investigated how TM and L2 motivation interact with each other. The participants were 154 school-level teachers with a range of backgrounds (teaching experience, geographic areas, and school sectors). In the questionnaire, four scales were included: (a) autonomous motivation for teaching; (b) demotivators; (c) perceived burnout; and (d) L2 motivation. Fifteen teachers were interviewed in order to triangulate the survey results. Structural equation modeling showed that TM negatively predicted perceived burnout, suggesting that it can counter teachers’ emotional exhaustion and their perceived lack of personal accomplishment. Demotivators predicted TM positively, albeit weakly. L2 motivation was found to be only weakly related to TM. Qualitative findings indicated that teaching experience mediated the role that demotivators played in relation to TM. Experienced teachers, especially those who held intrinsic motivation to teach, channeled the impact of demotivators, including those relating to the pandemic, to a positive motivational force to teach. The study implies the importance of considering teachers as agents and devising an educational system in which their mental health is prioritized.